(untitled) (Swiss Medical Weekly, 2012)
PRINCIPLES: The nine equivalents of nursing manpower use score (NEMS) is frequently used to quantify, evaluate and allocate nursing workload at intensive care unit level. In Switzerland it has also become a key component in defining the degree of ICU hospital reimbursement. The accuracy of nurse registered NEMS scores in real life was assessed and error-prone variables were identified. METHODS: In this retrospective multicentre audit three reviewers (1 nurse, 2 intensivists) independently reassessed a total of 529 NEMS scores. Correlation and agreement of the sum-scores and of the different variables among reviewers, as well as between nurses and the reviewers’ reference value, were assessed (ICC, % agreement and kappa). Bland & Altman (reference value – nurses) of sum-scores and regression of the difference were determined and a logistic regression model identifying risk factors for erroneous assessments was calculated. RESULTS: Agreement for sum-scores among reviewers was almost perfect (mean ICC = 0.99 / significant correlation p <0.0001). The nurse registered NEMS score (mean ± SD) was 24.8 ± 8.6 points versus 24.0 ± 8.6 points (p <0.13 for difference) of the reference value, with a slightly lower ICC (0.83). The lowest agreement was found in intravenous medication (0.85). Bland & Altman was 0.84 ± 10, with a significant regression between the difference and the reference value, indicating overall an overestimation of lower scores (≤29 points) and underestimation of higher scores. Accuracy of scores or variables was not associated with nurses’ characteristics. CONCLUSIONS: In real life, nurse registered NEMS scores are highly accurate. Lower (≤29 points) NEMS sum-scores are overestimated and higher underestimated. Accuracy of scores or variables was not associated with nurses’ characteristics.